Dinamika Fungsi Sosial Organisasi Kemasyarakatan Antara Pemberdayaan Masyarakat dan Praktik Premanisme Pada Era Desentralisasi di Indonesia - Bonefasius Bao; M. Rusdianto Abu; Anitha Nurak; Hendry Bakri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Mass organizations (Ormas) in Indonesia perform a paradoxical dual role in the era of decentralization: contributing positively to community empowerment while simultaneously transforming into institutionalized thuggery actors. This study analyzes the duality of Ormas social functions by examining four integrated dimensions: community empowerment, thuggery practices, factors driving role shifts, and the effectiveness of regional policies and government oversight. The study employs a systematic literature review with a descriptive qualitative approach, utilizing content analysis and thematic synthesis of academic literature and regulations published between 2010 and 2025. The findings reveal that community empowerment operates through three patterns: solidarity-based social services, micro-economic strengthening, and skills training. Ormas thuggery is classified into territorial, functional, and political typologies that intersect in practice, constituting a self-reinforcing mechanism produced by the interaction of weak internal governance, decentralization incentives, and inadequate regulatory frameworks. The article argues that repressive approaches alone are insufficient; an integrated strategy combining institutional capacity-building, incentive-based regulatory reform, and strengthened public participation as external oversight is required.